Jack Bailey: A Texas Drover's Diary, 1868 - David Dary; Jack Bailey (Symphony in the Flint Hills, 2017)
Introduction: In the late nineteenth century, thousands sought adventure and fortune on the cattle trails. Unfortunately, few committed their experiences to writing. The journal of Jack Bailey, which records the activities of a Texas cowboy from August 5 to November 8, 1868, is the earliest known daily account of life on the trail in the years following the Civil War. [Note: materially originally published by David Dary (ed.) in A Texas Cowboy's Journal: Up the Trail to Kansas in 1868.
Keywords: Texas cowboys; journals; diaries; cattle drives; Kansas; cowboys